Identification of the Coiled‐Coil Domain as an Essential Methyl‐CpG‐Binding Domain Protein 3 Element for Preserving Lineage Commitment Potential of Embryonic Stem Cells. (15th July 2018) - Hirasaki, Masataka; Ueda, Atsushi; Asaka, Masamitsu N.; Uranishi, Kousuke; Suzuki, Ayumu; Kohda, Masakazu; Mizuno, Yosuke; Okazaki, Yasushi; Nishimoto, Masazumi; Sharif, Jafar; Koseki, Haruhiko; Okuda, Akihiko
Abstract: Embryonic stem cells (ESCs) exhibit two salient features beneficial for regenerative medicine: unlimited self‐renewal and pluripotency. Methyl‐CpG‐binding domain protein 3 (Mbd3), a scaffolding component of the nucleosome remodeling deacetylase complex, is a specific regulator of pluripotency, as ESCs lacking Mbd3 are defective for lineage commitment potential but retain normal self‐renewal properties. However, functional similarities and dissimilarities among the three Mbd3 isoforms (a, b, and c) have not been intensively explored. Herein, we demonstrated that Mbd3c, which lacks an entire portion of the MBD domain, exerted equivalent activity for counteracting the defective lineage commitment potential of Mbd3 ‐knockout ESCs. Our analyses also revealed that the coiled‐coil domain common to all three MBD3 isoforms, but not the MBD domain, plays a crucial role in this activity. Mechanistically, our data demonstrate that the activity of the coiled‐coil domain is exerted, at least in part, through recruitment of polycomb repressive complex 2 to a subset of genes linked to development and organogenesis, thus establishing stable transcriptional repression. Stem Cells 2018;36:1355–1367 Abstract : Methyl‐CpG‐binding domain protein 3 (Mbd3), a scaffolding component of nucleosome remodeling and deacetylation complex, is dispensable for self‐renewal, but essential for their differentiation potential of embryonic stem cells (ESCs). Mbd3 bears two prominent domains, that is, MBD and coiled‐coil domain. Our analyses revealed that coiled‐coil domain, but not MBD, is crucially involved in preserving differentiation potential of ESCs. Our analyses revealed that the coiled‐coil domain is involved in the recruitment of polycomb repressive complex 2 for establishing stable repression of genes related to development.